Geotechnical and Structural Engineering Congress 2016 2016
DOI: 10.1061/9780784479742.054
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Investigation of Factors Influencing the Dynamic Response of Buried Reinforced Concrete Culverts

Abstract: In the current practice of bridge engineering, structures are designed and evaluated using static loads. In order to account for the dynamic nature of the true loading condition, static vehicle loads are increased by a dynamic amplification factor (DAF). The DAF has been widely studied for conventional bridges and has been found to be a function of vehicle forcing frequency and the fundamental frequency of the bridge. As a simplification, many design codes determine the DAF factor based on common bridge charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Noting the discrepancies between observations made during field tests of culverts and the values of DAF from AASHTO, Wells (2016) concluded that AASHTO recommended values of DAF are too conservative. In addition, by performing a parametric study, Wells et al (2016) showed that parameters other than the fill depth affect DAF significantly. In a pioneering study, Turneaure et al (1911) reported the DAF's strong dependency on the span length of culverts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Noting the discrepancies between observations made during field tests of culverts and the values of DAF from AASHTO, Wells (2016) concluded that AASHTO recommended values of DAF are too conservative. In addition, by performing a parametric study, Wells et al (2016) showed that parameters other than the fill depth affect DAF significantly. In a pioneering study, Turneaure et al (1911) reported the DAF's strong dependency on the span length of culverts.…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of culverts under dynamic loading conditions has not been extensively explored. Recently, however, the topic of dynamic behavior of culverts seems to have gained interest (e.g., Chen and Harik 2012;Beben 2013;Wells 2016;Wells et al 2016). Among these studies, the experimental investigation performed by Beben (2013) found out that the value of DAF for culverts increases with increasing span length and decreasing fill depth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation